Removal of basic yellow dye molecules with chitosan-based magnetic field-sensitive particles from the aqueous solution - Ipek, Omer; Tasar, Seyda; Duranay, Neslihan (Elsevier Sci Ltd, 2025)
The study aimed to develop chitosan-based particle sorbents and evaluate their efficiency in removing reactive dyes from wastewater, leveraging chitosan's hydrophilic and positively charged properties. Polymeric particles were synthesized using a precipitation-aggregation method and characterized via analytical techniques. Sorption performance was tested using Basic Yellow 28 (BY28) dye under varying conditions of temperature, pH, sorbent dosage, dye concentration, and contact time. Optimal conditions were identified as 40 degrees C, pH 7, 0.2 g/L sorbent dosage, 75 mg/L dye concentration, and 180 min contact time, achieving a maximum sorption capacity of 330.96 mg/g. Experimental data were evaluated using isotherm models (Langmuir, Freundlich, Temkin, Dubinin-Radushkevich), with the Langmuir isotherm showing an R2 value close to one (0.998), indicating a strong fit. The theoretical maximum sorption capacity (qmax) ranging from 196.08 to 322.58 mg/g across different conditions. Kinetic studies revealed the pseudo-second-order model best described the sorption process, with maximum sorption capacities (qe,c) at different temperatures calculated at 243.90, 294.12, 312.50, and 333.33 mg/g at 25, 30, 35, and 40 degrees C, respectively. The endothermic nature of adsorption indicates improved efficiency at higher temperatures, aligning with industrial requirements. The study highlights the versatility of chitosan particles across a wide range of pH and temperatures, combining chemical and physical adsorption mechanisms. These particles demonstrate stability, efficiency, and eco-friendliness, making them suitable for sustainable water treatment. The findings reinforce the applicability of chitosan in addressing textile wastewater challenges, offering insights into optimization and scalability for industrial effluent management. The robustness of chitosan particles further underscores their potential for broader applications in wastewater treatment.
Keywords: Chitosan-based sorbents; Sorption efficiency; Basic yellow 28 (BY28); Sorption isotherms; Kinetic modeling